Socio-Cultural And Maternal Mental Health Factors In Stunting Among The Sasaq Tribe Central Lombok - Sulaiman, Lalu; Sastrawan; Muslim, Al; Husein, Lalu Muhammad Sadam (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: Stunting is one of the indicators of the success of a nation's development, especially development in the health sector. Stunting will not only affect the shape of children's body posture which is shorter than other children of the same age, but stunting can also have implications for children's cognitive abilities which determine the nation's competitiveness in the future. Objective: The general objective of this study is to explore socio-cultural factors and maternal mental health related to stunting. Method: The method used in this study is a qualitative-descriptive method with a content analysis approach. Data were collected through in-depth interviews using interview guidelines. Results: The results of this study indicate that the risk factors for stunting are high rates of child marriage, low family economic resources, high divorce rates, high rates of high-risk pregnancies and maternal mental health conditions. Based on the results of this study, it can be concluded that socio-cultural factors and maternal mental health conditions are determinants of stunting. From the results of this study, it is recommended that local governments empower adolescents to reduce the rate of child marriage in preventing maternal mental health disorders, for example by forming youth classes in each village as a forum to socialize the negative impacts of child marriage.